2015
DOI: 10.4238/2015.may.4.10
|View full text |Cite
|
Sign up to set email alerts
|

Expression of high-mobility group box protein 1 in diabetic foot atherogenesis

Abstract: ABSTRACT. The role of high mobility group box 1 (HMGB1) has been demonstrated in stroke and coronary artery disease but not in peripheral arterial occlusive disease (PAOD). The pathogenesis of HMGB1 in acute and chronic vascular injury is also not well understood. We hypothesized that HMGB1 induces inflammatory markers in diabetic PAOD patients. We studied 36 diabetic patients, including 29 patients with PAOD, who had undergone amputation for diabetic foot and 7 nondiabetic patients who had undergone amputatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 39 publications
2
6
0
1
Order By: Relevance
“…In line with our studies, Feng and colleagues indicated that the interaction of HMGB-1 and its receptors triggered the oxidative stress in endothelial dysfunction [34]; similarly, serum HMGB-1 concentration was shown to reflect endothelial dysfunction in diabetes [22]. Recently, the increased HMGB-1 expression was found to be positively correlated with arterial stenosis, oxidative stress, and inflammation in diabetic patients with peripheral arterial occlusive disease [46]. In vitro experiment showed that microRNA-24 attenuated high-glucose-induced vascular smooth muscle cell proliferation and migration by targeting HMGB-1.…”
Section: Hmgb-1 and Cardiovascular Complicationssupporting
confidence: 80%
“…In line with our studies, Feng and colleagues indicated that the interaction of HMGB-1 and its receptors triggered the oxidative stress in endothelial dysfunction [34]; similarly, serum HMGB-1 concentration was shown to reflect endothelial dysfunction in diabetes [22]. Recently, the increased HMGB-1 expression was found to be positively correlated with arterial stenosis, oxidative stress, and inflammation in diabetic patients with peripheral arterial occlusive disease [46]. In vitro experiment showed that microRNA-24 attenuated high-glucose-induced vascular smooth muscle cell proliferation and migration by targeting HMGB-1.…”
Section: Hmgb-1 and Cardiovascular Complicationssupporting
confidence: 80%
“…This notion was strongly supported by a recent study showing higher serum HMGB-1 levels in patients with type 2 diabetes affected by PAD [93]. Furthermore, the expression of HMGB-1 increased in diabetic foot atherogenesis and arteriosclerosis obliterans [94,95].…”
Section: Figsupporting
confidence: 73%
“…In apolipoprotein E-deficient (apoE -/-) mice fed high-fat diet, treatment with neutralizing antibodies against HMGB-1 significantly prevented the development of atherosclerosis [10]. Further evidence revealed the critical role of HMGB-1 in human atherosclerosis lesions from the aorta, indicating high expression of HMGB-1 in carotid arteries [11], coronary arteries [12], and peripheral vessels [13]. In addition, macrophages have been considered to be primarily responsible for HMGB-1 expression in atherosclerosis [14], suggesting that the protein might promote macrophage-derived foam cells in plaques.…”
Section: Introductionmentioning
confidence: 99%